1965
DOI: 10.1152/ajplegacy.1965.209.5.986
|View full text |Cite
|
Sign up to set email alerts
|

Changes in type of hemoglobin during experimental hemorrhagic anemias in sheep

Abstract: A new hemoglobin was produced in sheep with Hb A during experimental anemias. This hemoglobin, called Hb Aα, had different electrophoretic characteristics and denatured with alkali at a faster rate than normal Hb A. It also showed electrophoretic differences to Hb B and Hb F. Hb Aα was located almost entirely in the reticulocytes produced during the anemia. The reticulocytes produced in anemic sheep with Hb B contained a hemoglobin which showed only minor differences from the normal hemoglobin on electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1968
1968
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The relationship between anaemia and the occurrence of haemoglobin C in animals of haemoglobin type A and AB was confirmed by partial exsanguination experiments, performed in a similar way to those described by van Vliet and Huisman (1964), Blunt (1965) and Kitchen et al (1968). In six sheep with haemoglobin type AB and in one animal with type A the abnormal haemoglobin was produced after about three weeks, while 16 animals of haemoglobin type B never developed the C band of haemoglobin.…”
Section: Blood Grps Biochem Genet 2 (1971)supporting
confidence: 59%
“…The relationship between anaemia and the occurrence of haemoglobin C in animals of haemoglobin type A and AB was confirmed by partial exsanguination experiments, performed in a similar way to those described by van Vliet and Huisman (1964), Blunt (1965) and Kitchen et al (1968). In six sheep with haemoglobin type AB and in one animal with type A the abnormal haemoglobin was produced after about three weeks, while 16 animals of haemoglobin type B never developed the C band of haemoglobin.…”
Section: Blood Grps Biochem Genet 2 (1971)supporting
confidence: 59%
“…Striking increases of Hb F have been seen in patients with juvenile chronic granulocytic leukaeinia (Maurer et al, 1972). In some animals, anaemia and hypoxia lead to switching of adult haemoglobin types (Blunt, 1965), and recent evidence indicates that this change is mediated by erythropoietin (Adamson & Stamatoyannopoulos, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…(c) Haemoglobin C. Huisman, van der Helm, Visser & van Vliet (1959) noticed that the relative proportions of HbA and HbB in the blood of HbAB-type sheep changed when they were severely anaemic as a result of infestation with Strongylus. Later it was observed that when sheep of Hb type A or AB are severely anaemic as a result of haemorrhage or worm infestation, the production of HbA ceases and another haemoglobin is produced Braend, Efremov & Helle, 1964;van Vliet & Huisman, 1964;Blunt, 1965). This was named 'C' by van Vliet & Huisman and 'N' by Braend et al, it only occurs in sheep which carry the gene for A haemoglobin.…”
Section: (6) Frequencies In Diyerent Breedsmentioning
confidence: 99%